ENHANCING PRONUNCIATION THROUGH FOLKLORE BASED ROLE PLAY: EVIDENCE FROM INDONESIAN EFL STUDENTS (Research And Development Journal Of Education (RDJE), 2026)
Pronunciation is a key but often neglected element of oral communication among English as a Foreign Language (EFL) students in Indonesia. Conventional teaching methods primarily concentrate on mechanical drills, which provide little communicative exposure. This study examined the effectiveness of a folklore-based role play method in developing students' pronunciation ability at MTsN 8 Tulungagung. The study employed a one-group pre-test–post-test design with eighth-grade students, who learned from Indonesian folktales (e.g., Timun Mas, Malin Kundang) adapted into English scripts for interactive role-plays. Quantitative data were collected from pre-test and post-test pronunciation assessments, scored using a valid rubric covering accuracy, fluency, stress, and intonation. The results revealed a notable improvement in students’ pronunciation performance following the implementation of the folklore-based role play, indicating that the treatment had a significant positive effect. These findings suggest that contextualized role play activities rooted in local culture can provide meaningful communicative practice, enhance learner motivation, and substantially improve pronunciation skills. The study thus contributes to pronunciation pedagogy by integrating cultural familiarity as both a motivational and linguistic resource in EFL classrooms.
Keywords: Role Play; Indonesian Folklore; Pronunciation Proficiency; EFL Learning; Communicative Pedagogy